Abdominal fat interacts with PNPLA3 I148M, but not with the APOC3 variant in the pathogenesis of liver steatosis in chronic hepatitis C. Issue 8 (7th January 2013) - Zampino, R.; Coppola, N.; Cirillo, G.; Boemio, A.; Pisaturo, M.; Marrone, A.; Macera, M.; Sagnelli, E.; Perrone, L.; Adinolfi, L. E.; Miraglia del Giudice, E.
Summary The patatin‐like phospholipase domain‐containing 3 gene (PNPLA3) and the apolipoprotein C3 gene (APOC3) have been studied in relation to liver steatosis and liver disease outcome. The aim of this study was to evaluate the influence of PNPLA3 p.I148M and APOC3 rs2854116 and rs2854117 polymorphisms on the clinical and histological presentation of chronic hepatitis C in an Italian population and their relationship with viral and anthropometric parameters. Patients with hepatitis C (n = 166) entered the study receiving a clinical, histological, virological and biochemical evaluation. APOC3 (rs2854116 and rs2854117) and PNPLA3 (p.I148M) variants were genotyped. PNPLA3 polymorphisms were associated with liver steatosis, which was significantly higher in patients with p.148I/M (P = 0.034) and p.148M/M (P = 0.004) variants than those homozygous for the PNPLA3 wild type. Excluding patients with HCV genotype 3, the association with liver steatosis and PNPLA3 variants was more marked (p.148I/I genotype vs p.148I/M, P = 0.02, and vs p.148M/M, P = 0.005). The APOC3 polymorphism was not associated with any of the evaluated parameters. Among the interacting factors, BMI and waist circumference correlated with liver steatosis (P = 0.008 and 0.004, respectively). Relationship between waist circumference and liver steatosis was analysed for the different PNPLA3 genotypes. Homozygous 148M patients showed a stronger correlation between waist circumference and steatosis than those carrying the other genotypes (P = 0.0047). In our hepatitis C‐infected population, the PNPLA3 polymorphism influenced the development of liver steatosis, but not fibrosis progression. APOC3 polymorphisms had no effect on the development of steatosis and no influence on the PNPLA3 polymorphism. The amount of abdominal fat can increase the association of PNPLA3 p.I148M with liver steatosis.